2012
DOI: 10.1177/1367006911435594
|View full text |Cite
|
Sign up to set email alerts
|

The syntax-semantics of bare and definite plural subjects in the L2 Spanish of English natives

Abstract: This study investigates the extent to which advanced native-English L2 learners of Spanish come to acquire restrictions on bare plural preverbal subjects in L2 Spanish (e.g. gatos "cats" vs. definite plurals such as los gatos "the cats"). It tests L2 knowledge of available semantic readings of bare plurals and definite plurals in Spanish, where [+specific] and [+generic] interpretations are syntactically represented differently from English. Assuming L1 transfer, and in view of a potential subset/superset rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Current studies have begun to simultaneously evaluate the importance of both Semantics and syntactic concepts in the process of language production (e.g., Cuza, Guijarro-Fuentes, Pires, & Rothman, 2013;Gil & Marsden, 2010;Han & Liu, 2013;Ko, Perovic, Ionin, & Wexler, 2008). For example, Beyersdorfer and Schauer (1989), among others, describes the relationship between teaching Semantics and improving writing skills.…”
Section: The Studymentioning
confidence: 99%
“…Current studies have begun to simultaneously evaluate the importance of both Semantics and syntactic concepts in the process of language production (e.g., Cuza, Guijarro-Fuentes, Pires, & Rothman, 2013;Gil & Marsden, 2010;Han & Liu, 2013;Ko, Perovic, Ionin, & Wexler, 2008). For example, Beyersdorfer and Schauer (1989), among others, describes the relationship between teaching Semantics and improving writing skills.…”
Section: The Studymentioning
confidence: 99%
“…CHARACTERIZATION OF FIRST language (L1) transfer effects has received growing attention in the second language (L2) acquisition of article systems (e.g., Cuza et al, 2012;Ionin, Ko, & Wexler, 2004;Ionin & Montrul, 2010;Ionin, Montrul, & Crivos, 2013;Ionin at al., 2011;Montrul & Ionin, 2012). This growing attention has been motivated in part by the well-documented errors involving definite and indefinite articles cross-linguistically (see García-Mayo & Hawkins, 2009, for an overview).…”
Section: Thementioning
confidence: 99%
“…The distribution, use, and omission of definite articles in generic contexts is much more complex than in inalienable possession. Cuza et al (2012) examined the extent to which advanced English-speaking learners acquire Spanish definite plurals that encode generic and specific readings (e.g., los gatos 'the cats' vs. gatos 'cats'). Starting from the assumption that learning is easier than unlearning, the task of Englishspeaking learners of Spanish was characterized as a remapping task of expansion, since they must come to permit both the generic interpretation and the specific interpretation for definite plurals.…”
Section: Acquisition Of Plural Noun Semantics In L2 Studiesmentioning
confidence: 99%
“…Certain nominal semantic features (e.g., definiteness, specificity) regulate the use of articles (definites versus indefinites) and demonstratives, creating an area of difficulty for learners that might be compounded by the fact that articles and demonstratives also reflect morphosyntactic agreement for gender and number (see below for details). To date, article use in L2 Spanish has received a modest amount of attention in the literature (e.g., Cuza, Guijarro-Fuentes, Pires and Rothman, 2013a;Ionin, Montrul and Crivos, 2013;Montrul and Ionin, 2012). Typically, English-speaking learners of Spanish and other Romance languages such as Italian (see Slabakova, 2006) are charged with the task of unlearning the one-to-one mapping of definiteness vs. genericity expressed in English through definite plurals (e.g., The elephants seem nervous) and bare plurals (e.g., Elephants have trunks), respectively, since Spanish uses definite plurals in both cases.…”
Section: Acquisition Of Properties Related To the Nominal Domainmentioning
confidence: 99%
“…Furthermore, L1 English learners have to reconfigure the semantics of bare plurals in L2 Spanish, since these can have an existential reading (e.g., Animales de todo tipo salían de las jaulas del zoo, 'Animals of all kinds came out of the zoo's cages') but not a generic one (*Animales son seres vivos, 'Animals are living beings', where the article "los" would be obligatory). Research on this topic has shown that, by advanced stages of proficiency, L1 English L2 Spanish learners appear to have native-like knowledge of the distribution of plural subject expressions in Spanish, despite the asymmetry between their native and their second language (e.g., Cuza et al, 2013a).…”
Section: Acquisition Of Properties Related To the Nominal Domainmentioning
confidence: 99%